Evaiuation of Cracks Propagation in Retroflllings with Cinalloy Amalgam - Zarrabian M; Amin- (Tehran University of Medical Sciences, 2000)
One of the major goals of preradicular surgery is to create a good apical seal. This can be done by sectioning approximately one third of the apex, preparation of a class I cavity, and filling with a biocompatible material. The purpose of this in vitro study was to compare crack propagation in retro filling with two commercially available amalgams. Thirty-four extracted single rooted teeth were divided into two groups. After instrumentation and filling with Gutta percha by lateral condensation method, three millimeter of apex was resected and retro preparations were done by a low speed hand piece and '/> round bur. Then cavities were filled with cinalloy and luxalloy amalgam in-group "one" and "two" respectively. The surface of resected root ends was examined in two stages, after doing retro preparation and retro filling and the presence of any cracks or structural changes was inspected by stereomicroscope 50x. Regard to number and type of cracks, the result of this study showed that there was no significant difference between cinalloy or luxalloy retro fillings. By considering the conditions of this study, cinalloy amalgam can be used as a retro filling material.